Fast Association Process (FAP) of Beacon Enabled for IEEE 802.15.4 in Strong Mobility - Muhammad, Javed; Kartinah, Zen; Halikul, Lenando; Hushairi, Zen (2013)
In strong mobility the mobile node association with a coordinator (static or mobile) is an important part of IEEE802.15.4 protocol. This research analyzes the mobile node association attempt process flows in detail. This research also proposes an enhanced association procedure names Fast Association Process (FAP) in strong mobility. FAP is introduced with new Association_Data request MAC command that increases the association period and provides fast association process in strong mobility. It reduces the redundant service primitives, avoid collision and decrease association attempt process delay. Comparing FAP with the original IEEE802.15.4 protocol, the number of association service primitives in FAP is 67% less than the original protocol, and the simulation results show that the association attempt time decreases 75%. FAP will get fast association attempt as the number of mobile nodes increased and nodes having strong mobility. It can be widely used in mobile wireless sensor network application.